Osteoprotegerin Is an Independent Predictor of Vascular Events in Finnish Adults With Type 1 Diabetes - Gordin, Daniel (American Diabetes Association, 2013)
OBJECTIVE: Osteoprotegerin (OPG) is involved in the process of vascular calcification. We investigated whether OPG is associated with the development and progression of diabetes complications in adults with type 1 diabetes (T1D). RESEARCH DESIGN AND METHODS: Serum OPG was measured in 1,939 adults with T1D participating in the Finnish Diabetic Nephropathy (FinnDiane) Study. Patients with end-stage renal disease (dialysis or transplantation) at baseline were excluded from analysis. Data on cardiovascular (CV) events and mortality during follow-up were verified from hospital discharge registries (ICD codes) and the Finnish National Death Registry, respectively. The follow-up time was 10.4 ± 2.0 (mean ± SD) years. RESULTS: Only patients with macroalbuminuria and/or renal impairment had elevated OPG concentrations, when compared with participants without overt kidney disease. Patients with retinopathy or CV disease also had higher OPG concentrations, but this was attributable to their higher frequency of chronic kidney disease. OPG predicted an incident CV event (hazard ratio 1.21 [95% CI 1.01–1.45]; P = 0.035) and peripheral vascular disease/amputation events (1.46 [1.13–1.88]; P = 0.004) during follow-up. CONCLUSIONS: We showed that serum OPG is an independent predictor of CV complications. OPG may be directly involved in extraosseous calcification, resulting in stiffening of the arteries and subsequent vascular insufficiency in patients with T1D.